The Effect of Accelerated Transcranial Magnetic Stimulation on Insomnia Severity and Sleep Quality in Patients With Treatment-Resistant Depression - Hilal Uygur; Rukiye Tekdemir; Hülya Ertekin (Sleep Medicine Research)
Background and Objective Insomnia severity and poor sleep quality are linked with a poor response to depression treatments. Furthermore, they may heighten suicide risk, necessitating careful management and treatment of insomnia. This study explored how accelerated transcranial magnetic stimulation (aTMS) affects insomnia severity and sleep quality in patients with treatment-resistant depression (TRD). Methods This retrospective study included files from 28 patients with TRD who met specific inclusion and exclusion criteria. We assessed changes in insomnia severity and sleep quality by comparing scores before and after aTMS treatment. All patients underwent 50 sessions of intermittent theta burst stimulation over the left dorsolateral prefrontal cortex across 10 days. Results The mean age of the patients was 40.82±12.03 years. Before aTMS, the Insomnia Severity Index (ISI) score was 18.21±9.45, and the Pittsburgh Sleep Quality Index (PSQI) score was 12.85±4.75. After aTMS, ISI and PSQI scores improved to 5.75±6.70 and 6.75±5.01, respectively. The mean reductions in ISI and PSQI scores post-aTMS were 12.46 and 6.10, with Cohen’s effect sizes of 1.51 and 1.26, respectively. The sub-dimensions of subjective sleep quality and daytime dysfunction showed the most significant decreases, while sleep duration decreased the least. Improvements in all sleep parameters were statistically significant. Conclusions aTMS significantly alleviated insomnia severity and enhanced sleep quality in patients with TRD within just two weeks.